KORELASI ANTARA MINAT DENGAN PRESTASI BELAJAR BAHASA JERMAN MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JERMAN FAKULTAS BAHASA DAN SASTRA UNIVERSITAS NEGERI MAKASSAR - Misnawaty Usman; Burhanuddin Burhanuddin; Nurming Saleh (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2022)
This research is ex post facto correlational nature that aims to determine how the correlation between interest in learning the German language learning achievements of students of the German language education FBS-UNM. The population in this study were students of the even semester academic year  2020-2021German language education study pogram FBS-UNM totaled 42 students .Its well as a sample in this study (total sample). Data collection techniques used in this study is Lickert Scale and tests. Data were analyzed using correlation techniques "Product Moment". Hypothesis testing results show that there is a significant positive relationship between student interest in learning German with the achievement of students in learning German. This means that the factor of interest of students to learn the German language student achievement semester of academic year 2020-21 majoring in foreign language education study programs German language education. The higher the students' interest in learning the German language lessons, the higher the learning achievements of their German language. KeyWords: correlation, interest, and learning achievement